Pengaruh Model Pembelajaran Reciprocal Teaching (Pengajaran Terbalik) terhadap Hasil Belajar Siswa pada Pokok Bahasan Pencemaran Lingkungan - Diah Khusnia; Dede Nuraida (Universitas Sebelas Maret, 2017)
This research was aimed to know the differences of the result of studying science between students who got Reciprocal Teaching learning model and the students who got the conventional teaching learning model for grade VII semester II at MTs. Manba’il futuh jenu Sub-district, in academic year 2016/2017. This research has 3 steps: 1) preparation stage; 2) Implementation stage; 3) Evaluation Phase.This research is a quasi-experimental research. The population of this research was 64 students of grade VII semester II at MTs. Manba’il futuh jenu Sub-district. The sample of this research was 32 students from class VIIG and 32 students from class VIIH of grade VII semester 2 at MTs Manba’il futuh jenu Sub-district. The data was collected by using objective test instrument and was being analyzed by using the analysis of Descriptive Statistic and Inferential Statistic Test (t-test). This research showed that there was a significant between students who got Reciprocal Teaching learning model and the students who got the conventional teaching learning model. It was seen from the average score of experimental group which was 81.94. It was higher than the average of control group which was 70,83. It can be concluded that the implementation of Reciprocal Teaching learning model influenced the result of studying science for grade VIIG semester2 at MTs. Manba’il futuh , jenu Sub-district, in academic year 2016/2017.